(untitled) (Modern education and development, 2025)
This paper provides a detailed exploration of three significant but often underrepresented semantic categories in linguistics: paronyms, hyperonyms, and hyponyms. These semantic classes, while not as commonly addressed as synonyms or antonyms, play a crucial role in understanding the organization and function of language. Paronyms are words that are similar in form but differ in meaning, often causing confusion in communication and requiring careful attention in both language learning and stylistic analysis. Hyperonyms and hyponyms, on the other hand, illustrate hierarchical relationships in the lexicon — hyperonyms representing broader, more general categories, and hyponyms specifying narrower, more particular concepts within those categories. This classification of words helps build mental lexical networks that enhance both linguistic competence and cognitive processes such as categorization, abstraction, and inference. The study emphasizes the importance of these semantic relationships in various linguistic disciplines, including lexicology, lexicography, and computational linguistics. Additionally, it highlights the relevance of paronymic and hyponymic structures in artificial intelligence, particularly in natural language processing and semantic search engines. Understanding these relationships not only supports language comprehension but also facilitates more effective teaching methodologies, improves translation accuracy, and fosters a deeper appreciation for the structure and evolution of language. As language continues to evolve and technology becomes more language-dependent, awareness of these semantic classes becomes increasingly valuable for both linguists and practitioners in related fields.